Computational decomposition reveals reshaping of the SARS‐CoV‐2–ACE2 interface among viral variants expressing the N501Y mutation. Issue 12 (13th September 2021) - Socher, Eileen; Conrad, Marcus; Heger, Lukas; Paulsen, Friedrich; Sticht, Heinrich; Zunke, Friederike; Arnold, Philipp
Abstract: Variants of concern of the SARS‐CoV‐2 virus with an asparagine‐to‐tyrosine substitution at position 501 (N501Y) in the receptor‐binding domain (RBD) show enhanced infectivity compared to wild‐type, resulting in an altered pandemic situation in affected areas. These SARS‐Cov‐2 variants comprise the two Alpha variants (B.1.1.7, United Kingdom and B.1.1.7 with the additional E484K mutation), the Beta variant (B.1.351, South Africa), and the Gamma variant (P.1, Brazil). Understanding the binding modalities between these viral variants and the host cell receptor ACE2 allows to depict changes, but also common motifs of virus–host cell interaction. The trimeric spike protein expressed at the viral surface contains the RBD that forms the molecular interface with ACE2. All the above‐mentioned variants carry between one and three amino acid exchanges within the interface‐forming region of the RBD, thereby altering the binding interface with ACE2. Using molecular dynamics (MD) simulations and decomposition of intermolecular contacts between the RBD and ACE2, we identified phenylalanine 486, glutamine 498, threonine 500, and tyrosine 505 as important interface‐forming residues across viral variants. However, especially the N501Y exchange increased contact formation for this residue and also induced some local conformational changes. Comparing here, the in silico generated B.1.1.7 RBD–ACE2 complex with the now available experimentally solved structure reveals very similar behavior during MD simulation. We demonstrate, how computational methods can help to identify differences in conformation as well as contact formation for newly emerging viral variants. Altogether, we provide extensive data on all N501Y expressing SARS‐CoV‐2 variants of concern with respect to their interaction with ACE2 and how this induces reshaping of the RBD–ACE2 interface. Abstract :